2014
DOI: 10.1371/journal.pone.0098319
|View full text |Cite
|
Sign up to set email alerts
|

MHC-Matched Induced Pluripotent Stem Cells Can Attenuate Cellular and Humoral Immune Responses but Are Still Susceptible to Innate Immunity in Pigs

Abstract: Recent studies have revealed negligible immunogenicity of induced pluripotent stem (iPS) cells in syngeneic mice and in autologous monkeys. Therefore, human iPS cells would not elicit immune responses in the autologous setting. However, given that human leukocyte antigen (HLA)-matched allogeneic iPS cells would likely be used for medical applications, a more faithful model system is needed to reflect HLA-matched allogeneic settings. Here we examined whether iPS cells induce immune responses in the swine leukoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 39 publications
1
31
0
Order By: Relevance
“…However, the degree of immunogenicity of differentiated derivatives of iPS cells upon transplantation back into the individual from whom they were initially derived remains a question (Bjorklund and Kordower, 2013;Morizane et al, 2013;Guha et al, 2013;Araki et al, 2013;Zhao et al, 2011;Mizukami et al, 2014;Lee et al, 2013;Kim, 2011;Lindvall et al, 2012;Parmar and Bjorklund, 2012). For example, previous work in Macaca fasicularis demonstrated that an autologous graft can survive transplantation into a NHP brain (Morizane et al, 2013;Wang et al, 2015), and provided proof-of-concept that patient-specific neurons can be produced for the purposes of autologous transplantation therapy in patients with PD.…”
Section: The Nhp Model For Transplantation Therapy: Immunological Conmentioning
confidence: 99%
“…However, the degree of immunogenicity of differentiated derivatives of iPS cells upon transplantation back into the individual from whom they were initially derived remains a question (Bjorklund and Kordower, 2013;Morizane et al, 2013;Guha et al, 2013;Araki et al, 2013;Zhao et al, 2011;Mizukami et al, 2014;Lee et al, 2013;Kim, 2011;Lindvall et al, 2012;Parmar and Bjorklund, 2012). For example, previous work in Macaca fasicularis demonstrated that an autologous graft can survive transplantation into a NHP brain (Morizane et al, 2013;Wang et al, 2015), and provided proof-of-concept that patient-specific neurons can be produced for the purposes of autologous transplantation therapy in patients with PD.…”
Section: The Nhp Model For Transplantation Therapy: Immunological Conmentioning
confidence: 99%
“…Furthermore, the methodology for generation of iPS cells is relative simple and and is thought to be easily transferable to other mammalian species. Thus farm animal models may turn out to be ideally suited to determine required cell doses, to assess long-term performance, tumorigenicity, applications methods and fate of transplanted cells [38][39][40][41] . Recent advances in genetic engineering of farm animals allow the generation of precise genetic modifications [42][43][44][45][46][47] , such as the production of immunodeficient pigs [48] which will be instrumental for further advances in preclinical testings of new cell therapies.…”
Section: Discovery Of Induced Pluripotencymentioning
confidence: 99%
“…Hence, animal models could be contributed tremendously to a better understanding of disease mechanisms and therapeutic interventions. In addition, iPS cells from monkey [5] , porcine [41,26] , canine [8] and cattle [9] would be useful in animal biotechnology such as making precise genetic engineering for improved production traits and products [137,138] .…”
Section: Modeling Of Human Diseases and Preclinical Trialsmentioning
confidence: 99%
“…Concerns remain for allogeneic immunologic events induced due to not only HLA disparity but also natural killer (NK) cell systems. Extensive evaluations of allogeneic responses in this setting have been reported [10][11][12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%